Relationship between lower body muscle architecture and lunges performance - Md Nadzalan Ali, Mohamad Nur Ikhwan, Low Jeffrey Fook Lee, Chinnasee Chamnan, (Universiti Pendidikan Sultan Idris, 2016)
Relationship between lower body muscle architecture and lunges performance by Md Nadzalan Ali, Mohamad Nur Ikhwan, Low Jeffrey Fook Lee, Chinnasee Chamnan,